New species of the Genus Afrikanetz Yakovlev, 2009 from Republic of Côte d’Ivoire (Lepidoptera: Cossidae, Cossinae) - Yakovlev, R. Y. (SHILAP Revista de lepidopterología, 2022)
The article describes Afrikanetz schouteni Yakovlev, sp. n., distributed in the Republic of Côte d’Ivoire. The article has two illustrations.